Interview with Juana Gutierrez, environmental activist with the Mothers of East Los Angeles, Ca. . Transcripts in archive M. Bouvard - Bouvard, Marguerite Guzmán.
Interview with Juana Gutierrez, environmental activist with the Mothers of East Los Angeles, Ca. Transcripts in archive M. Bouvard.